Performance Analysis and Pacing Strategies in Sprint Freestyle Swimming at the 2025 SEA Games: A Case Study of the Men's 100m and 50m Events - Bazuri Fadillah Amin; Del Asri; Eko Juli Fitrianto; Made Bang Redy Utama; Wita Septiani Rahmaputri; Muhammad Gilang Ramadhan; Sri Indah Ihsani; Ayu Purnama Wenly (Bulletin of Community Engagement, 2025)
This study aims to analyze pacing strategies, the influence of the start reaction, and performance consistency of male athletes in sprint freestyle swimming events (50m and 100m) at the 2025 SEA Games. The research used a descriptive quantitative approach with a case study design. Secondary data were analyzed from the finals of both events, including final times, reaction times (RT), and split times. Descriptive and comparative statistical analyses were conducted to evaluate pacing patterns, the relationship between RT and final results, and the performance of athletes competing in both events. All athletes in the 100m event applied a positive split pattern, with an average speed decrease of 2.26 seconds in the second half. The start reaction did not significantly correlate with the final time in the 50m (r=0.15; p=0.71) or the 100m (r=0.45; p=0.26). Athletes competing in both events showed high ranking consistency. The age group <20 years tended to have a smaller pacing difference (2.16 seconds) compared to older athletes. Pacing strategies at the regional level are still dominated by the conventional approach (positive split). The main determinant of performance is not the start reaction, but pure swimming speed and technical efficiency.